Integrated Analysis of Inverter Temperature Effects, Protection, and Zero-Export Control in On-Grid PV Systems - Achmad Zidan Alamsyah; Muhamad Iqbal Risantia; Wahyu Deka Setiyawan; Nur Alif Mardiyah; Ilham Pakaya (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study presents an integrated field-based assessment of inverter-room temperature effects, protection-system readiness, and zero-export control in a 33.04 kWp grid-connected photovoltaic (PV) system at an industrial facility in Indonesia. The study addresses a practical reliability gap by combining thermal analysis, before-interconnection protection review, and power-flow regulation in one framework. Field observations were conducted for two operating days from 10:00 to 15:00 at 15-minute intervals. The thermal assessment used 12 paired A/C ON and A/C OFF intervals with irradiance differences of 2-10 W/m² to minimize irradiance-related bias. A paired t-test, correlation analysis, and linear regression were applied. Increasing inverter-room temperature from 21.66 °C to 28.73 °C reduced average inverter output from 24.156 kW to 23.621 kW. The average reduction was 0.535 kW or 2.21%, with empirical sensitivity of 0.076 kW/°C and a statistically significant paired-output difference (p < 0.001). The protection assessment confirmed that the before-interconnection panel supports overcurrent interruption, surge mitigation, grounding, and local isolation, although detailed fault-current coordination and grounding-resistance tests were outside the present scope. Zero-export control reduced surplus grid export from 66.18 kWh to 0.00 kWh; the potential curtailed-energy share was 38.56%. These findings demonstrate that thermal control, protection readiness, and export regulation are complementary measures for improving industrial on-grid PV reliability in tropical operating conditions.. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate Action